Space-time dynamics of attacks by hematophagous bats and geographic access to health care in a region of Mexico. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
The objective of this study was to estimate the spatial patterns in rates of aggression by vampire bats (Desmodus rotundus) and identify human populations with limited geographic access to medical service with post-exposure prophylaxis. METHOD: A set of points georeferenced with case reports of aggression by bats in humans was used to model the rates-adjusted of aggression against residents of local communities in the south of the State of Mexico. A continuous prediction area was constructed based on the rates of aggression from events during the year 2000 (outbreak of rabies cases in animals, and attacks to humans) and during the period 2001 to 2009 (stability in the frequency of cases) using a spatial interpolation method (Poisson- Kriging). The coverage areas of health services were calculated through a network analysis, estimating travel times (30 to 60 minutes) to the nearest hospital unit. Both estimates were integrated with risk maps. RESULTS: Two thousand one hundred ninety people of different sexes and ages were attacked by vampire bats in the region; 94.8% of attacks were recorded in the municipalities of Tejupilco and Luvianos. In 2000, there was an outbreak of rabies in animals, with an increase of 74.4% in the number of attacks (1629 recorded). During 2001-2009, the rate of aggression by gender showed a significant increase in women (58.6%) in contrast to men (41.4%). By age group, the highest percentage of attacks was from ages 1 to 19. By anatomical region more attacks were recorded in the upper extremities with 784 cases. Seasonal aggression was observed, with greater frequency in the months of April to August. Mapping was developed for both Poisson-Kriging model designs, a trend toward a higher rate of aggressions being observed in both models in the north-west, in the municipality of Luvianos. This distribution and seasonality is related to several factors such as: high production and marketing of livestock in the municipality, the physical and geographical conditions in the region that favor the survival of hematophagous bat, and socio-economic conditions with high level of social vulnerability and limited access to health services of basic levels. CONCLUSION: The Geographic Information Systems in Health provide a tool for geostatistical analysis, management and planning which is essential because it is possible to address the risk of aggression toward humans by vampire bats from a perspective which is spatial, systemic, multi-causal and interdisciplinary. Acknowledgements The authors wish to acknowledge to María Eugenia Jaimes from Comite de Fomento y Protección Pecuaria del Estado de México. Facultad de Geografía-UAEMex for his assistance with the creation of cartography. MD Gabriel O’shea Cuevas from Instituto de Salud del Estado de México.